MBR 공정에서 포기방법에 따른 막오염 특성 - 이준명; 최창규; 이광호 (한국수처리학회지, 19(6), 2011)
This study investigated the characteristics of the membrane fouling according to aeration conditions between continuous aeration and intermittent aeration estimating the permeability resistance on the passive adsorption. It also examined the concentration of eEPS and sEPS to find out the recovery rate of membrane after cleaning methods(physical and chemical cleaning). EPS (Extra Polymeric Substances) was mainly reported as membrane foulants, especially like protein and carbohydrate etc. EPS is classified eEPS (extracted EPS) and sEPS (soluble EPS). As the result, the permeability resistance of the continuous aeration is steeply increased compared to the intermittent aeration, because long aeration time led to the production of the much membrane foulants. Even though the COD loads were the same in two conditions, the EPS concentration of continuous aeration was higher than intermittent aeration. Also, sEPS concentration is getting increased as the operation continued, because membrane foulants was in the soluble state separated from the microbe. Therefore, we found that prolonged time of aeration could led to high EPS concentration by promoting the growth of biological metabolism, and the rise of EPS deteriorated membrane permeability. This study investigated the characteristics of the membrane fouling according to aeration conditions between continuous aeration and intermittent aeration estimating the permeability resistance on the passive adsorption. It also examined the concentration of eEPS and sEPS to find out the recovery rate of membrane after cleaning methods(physical and chemical cleaning). EPS (Extra Polymeric Substances) was mainly reported as membrane foulants, especially like protein and carbohydrate etc. EPS is classified eEPS (extracted EPS) and sEPS (soluble EPS). As the result, the permeability resistance of the continuous aeration is steeply increased compared to the intermittent aeration, because long aeration time led to the production of the much membrane foulants. Even though the COD loads were the same in two conditions, the EPS concentration of continuous aeration was higher than intermittent aeration. Also, sEPS concentration is getting increased as the operation continued, because membrane foulants was in the soluble state separated from the microbe. Therefore, we found that prolonged time of aeration could led to high EPS concentration by promoting the growth of biological metabolism, and the rise of EPS deteriorated membrane permeability. KCI Citation Count: 4